The endothelial injury technique using intravenous catheters: a new alternative method for developing atherosclerotic plaque models in Wistar rats - Ermawan, Romi; Pikir, Budi Susetyo; Mulyanto, Mulyanto; Utomo, Budi; Widjiati , Widjiati; Oktaviono, Yudi Her (Universitas Brawijaya, 2026)
Background: Developing an atherosclerotic plaque model is crucial in atherosclerosis research, as creating such a model remains a significant challenge. Objective: This study evaluates the endothelial injury technique using intravenous catheters as an alternative method for developing atherosclerotic plaque models in Wistar rats. Methods: This true experimental study employs a post-test-only control group design. Twenty-two adult male Wistar rats were randomly allocated into three groups: a control group, a treatment group that underwent a 6-week intervention, and another treatment group that underwent an 8-week intervention. The control group was fed a standard diet of 320 kcal per 100 grams, while both treatment groups received a high-fat diet of 414 kcal per 100 grams. In the second week, endothelial injury was induced in the left common carotid artery of both treatment groups using a 26G intravenous catheter. The parameters assessed in the atherosclerotic plaque model included matrix metalloprotease-9 expression, M1 macrophage activity, M2 macrophage activity, maximal intima thickness, and the degree of arterial stenosis. Result: The endothelial injury technique using intravenous catheters significantly impacted matrix metalloprotease-9 expression (p<0.001) in both the 6-week and 8-week treatment groups compared to the control group. In contrast, the treatment's effects on maximal intima thickness (p=0.003) and the degree of arterial stenosis (p=0.002) were statistically significant only after 8 weeks of intervention compared to the control group. Conclusion: The endothelial injury techniques using intravenous catheters can be considered an alternative method for developing atherosclerotic plaque models in Wistar rats. Although this new technique has several limitations, it holds promise for further development in future studies.